Financial income of social workers and self-care options in the Czech Republic - Stráský, Marek; Urban, David (Journal of nursing, social studies and public health, 2024)
This article deals with the relationship between social workers' self-care and financial income, which seems necessary for self-care. Self-care is typically considered an essential part of social work abroad. In social work, the importance of self-care is emphasised because it affects not only the quality of life of social workers but also their ability to perform their profession. Self-care is often mentioned as an essential part of social work, to which social workers are entitled and obliged to practice. This review is a secondary analysis of available data (financial and guaranteed income, cost of living, etc.). Suppose there is pressure on social workers to practice self-care. In that case, it is also necessary to address the prerequisites that enable or prevent it, and the financial aspect is the area that seems the most neglected - it may be the biggest and most challenging obstacle to overcome. This article proposes adjustments to ensure the financial possibilities of social workers' self-care. Insufficient self-care carries many risks, the most serious of which is burnout, which is also associated with a significant decrease in performance.